COMPLETE REMISSION OF ACUTE MYELOID LEUKEMIA IN INDUCTION AND CONSOLIDATION CHEMOTHERAPY WITHOUT BONE MARROW TRANSPLANTATION: LESSONS LEARNED FROM GOOD PRESENTATION CASE - Sri Hastuti, Tuti; Sumantri, Rachmat; Wijaya, Indra (Faculty of Medicine, Universitas Padjadjaran, 2019)
Acute myeloid leukemia (AML) is a clinically morphologically and genetically heterogeneous disease with variable responses to therapy. The majority of the patients eventually relapse and succumb to the disease. Therapeutic modalities of induction chemotherapy, consolidation, and bone marrow transplantation are intended to achieve complete remission. Induction therapy with cytarabine and anthracycline remains thestandard of care in AML. Consolidation treatment is necessary to prevent recurrence, which may reach 90% without this treatment. Options for consolidation therapy are conventional chemotherapy and bone marrow transplantation. Bone marrow transplantation represents the only realistic chance of long-term remission in patients with a high cytogenetic risk. The risk of recurrence of AML is determined mainly by the patient?s age and genetic factors. In younger patients, complete remission (CR) rates of ?80% may be achieved, with 5-year overall survival (OS) of 40%. InDr. Hasan Sadikin Hospital Bandung during the period of 2013-2018, 12 cases of LMA underwent chemotherapy. This case study discusses a young patient with AML who has successfully reached complete remission using induction and consolidation chemotherapy without bone marrow transplantation. Key words: Acute myeloid leukemia, chemotherapy, complete remission Remisi Lengkap Pasca Kemoterapi Induksi dan Konsolidasi Tanpa Transplantasi Sumsum Tulang pada Leukemia Mieloblastik AkutLeukemia mieloblastik akut adalah sekelompok penyakit yang memiliki gejala klinis, morfologi sel darah, kelainan genetik, dan respon terhadap terapi yang sangat bervariasi. Sebagian besar pasien leukemia mieloblastik akut (LMA) biasanya akan mengalami kekambuhan dalam perjalanan penyakitnya. Kejadian kekambuhan dalam 5 tahun sebesar 9% untuk kekambuhan di ekstramedulari dan 29% kekambuhan di sumsum tulang. Tujuan terapi pada LMA adalah mencapai remisi lengkap dan mencegah kekambuhan melalui modalitas kemoterapi dan transplantasi sumsum tulang. Transplantasi sumsum tulang diindikasikan pada pasien LMA dengan risiko sitogenetik yang tinggi. Tingkat remisi lengkap ?80% dapat dicapai, terutama pada pasien yang lebih muda dengan kelangsungan hidup keseluruhan 5 tahun 40%. Di Rumah Sakit Hasan Sadikin Bandung, selama kurun waktu 2013-2018 didapatkan 12 kasus LMA yang menjalani kemoterapi. Pada artikel ini didiskusikan 1 pasien LMA usia muda yang berhasil mencapai remisi lengkap dengan kemoterapi induksi dan konsolidasi tanpa menjalani transplantasi sumsum tulang dengan terapi pendukung yang optimal selama pemberian kemoterapi.Kata kunci : Leukemia mieloblastik akut, kemoterapi, remisi lengkap